DISCOBLOG UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI DAN PRESTASI BELAJAR EKONOMI BISNIS SISWA KELAS X AKL 2 SMK N 1 SUKOHARJO - Sidi, Purnomo (Jurnal Pendidikan Ilmu Sosial, 2020)
ThisÂ study aims to improve studentsâ€™ collaboration skills and learning achievement of Business Economics subject through the implementation of a blogâ€based Discovery Learning (DiscoBlog). The subject of this Classroom Action Research were 31 students of X AKL 2 class of SMK N 1 Sukoharjo in the even semester of the academic year 2019/2020. The data was collected using observation and tests. The observation was used to find out the studentsâ€™ collaboration skills in applying DiscoBlogthrough the observation sheet. The test was used to obtain the data about studentsâ€™ learning achievement of Business Economics subject through 25 multiple choiceâ€type questions. The data were analyzed by usingdescriptive quantitative through a mean score. The results revealed that there was an improvement in studentsâ€™ collaboration skills in applying DiscoBlog. It can be seen by the increase of collaboration skills score from 63,44 in preâ€cycle to 83,33. Besides, there was an improvement in studentsâ€™ learning achievement of Business Economics subject. The mean score showed a rise from 69,10 in preâ€cycle with the learning completion 54,84% to 80,97 with the learning completion 93,55%. Teachers might be able to apply these results to improve the learning quality of Business Economics subject.